Nano octahedral electrocatalyst as well as preparation and application thereof
By adopting a multi-stage structure Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst, the problems of high anode energy consumption and short activity of noble metal catalysts during electrolytic hydrogen production are solved, and energy consumption and selectivity are reduced during the electrocatalytic oxidation of PET plastic hydrolysate ethylene glycol, which is suitable for the upgrade and utilization of PET plastics and energy-saving and green hydrogen production.
Patent Information
- Application Number
- CN202411810747.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The prior art has problems such as high energy consumption, low efficiency and slow reaction kinetics in the process of electrolyzing water hydrogen production. The precious metal catalysts have short activity and high cost in the EGOR process, which limits the industrialization and promotion of technology.
A multi-stage structure Ru-(CoCu)2V2O7@Cu2O nanooctahedral electrocatalyst is used. This catalyst forms a core-shell structure by depositing a CoCu layer and a Ru layer on the surface of Cu2O nanooctahedral, combining the dual characteristics of precious metals and oxygen-friendly non-precious metals, reducing energy consumption and improving the selectivity of C2 products.
It realizes that in the electrocatalytic oxidation coupled cathode hydrogen production process of PET plastic hydrolysate ethylene glycol, it reduces energy consumption, improves selectivity and stability, and is suitable for the upgrade and utilization of PET plastics and energy-saving and green hydrogen production.
Smart Images

Figure CN119615268A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a nano octahedral electrocatalyst and the preparation and application thereof. Background Art
[0002] Hydrogen energy has the advantages of high combustion calorific value, no pollution, and zero emissions, and occupies an important position in future sustainable development. At present, more than 90% of hydrogen is produced by traditional fossil fuel steam reforming technology. This process will consume fossil resources and produce greenhouse gases, which is not conducive to environmental protection. In contrast, the electrolysis of water to produce hydrogen uses excess electricity generated by intermittent renewable energy (such as solar energy, wind energy, tidal energy, etc.) to drive water decomposition to produce high-purity hydrogen. Its technology is mature, the equipment is simple, and the reaction conditions are mild, and it has great application prospects. However, the electrolysis of water to produce hydrogen technology has problems such as high anode energy consumption, low efficiency, and slow reaction kinetics. Efficient catalysts are needed to improve energy conversion efficiency. Therefore, replacing the anode oxygen evolution reaction with thermodynamically more favorable small molecules (such as ethylene glycol, urea, etc.) electrooxidation is a hydrogen production strategy that has recently emerged.
[0003] As the most important high molecular polymer, plastic has multiple characteristics such as light weight, low cost and easy processing. It has been widely used in various fields such as daily packaging, building materials, electronics, medical equipment and energy storage, and has become a necessity for human social development and daily life. However, the huge market demand has led to a rapid increase in the global production of plastics, but it has also caused a huge amount of waste plastics to accumulate, causing irreparable damage to water sources, soil, air and oceans. With the development of renewable energy, the upgrading and utilization of plastics based on electrochemical catalytic technology coupled with hydrogen production is expected to become an important way to control environmental pollution and efficiently prepare green hydrogen.
[0004] At present, the electrocatalytic oxidation (EGOR) of PET plastic hydrolysate ethylene glycol (EG) coupled with cathode hydrogen production (HER) mainly relies on precious metal catalysts such as Ru, Pt, Pd, etc. For the EGOR process, precious metal catalysts tend to produce high value-added C2 products (such as glycolic acid GA, etc.), while non-precious metal catalysts tend to produce low value-added C1 products (such as formic acid, etc.). However, precious metal catalysts are severely limited by the high sensitivity of carbonyl intermediates, and their activity is generally lost rapidly within 10 hours. In addition, their high cost and scarce reserves objectively restrict the large-scale industrialization and promotion of this technology. Therefore, it is of great practical significance to develop an efficient, stable and inexpensive electrocatalyst to reduce energy consumption and improve selectivity. Summary of the invention
[0005] The purpose of the present invention is to provide a nano-octahedral electrocatalyst and its preparation and application to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention: a method for preparing a nano-octahedral electrocatalyst comprises the following steps:
[0008] (1) Preparation of Cu2O nano-octahedron: adding a mixed solution B of alkali and reducing agent to a mixed solution A of soluble inorganic copper salt and surfactant, heating for reaction, centrifugal washing, and drying to obtain the Cu2O nano-octahedron (template);
[0009] (2) dispersing the Cu2O nano-octahedron in a mixed solution of Na2S2O3, vanadate and cobalt salt, stirring for reaction, centrifuging for washing and drying to obtain a (CoCu)2V2O7@Cu2O core-shell structure intermediate (i.e., depositing a (CoCu)2V2O7 active layer on the surface of the Cu2O nano-octahedron);
[0010] (3) dispersing the (CoCu)2V2O7@Cu2O core-shell structure intermediate in a mixed solution of vanadate, ruthenium salt, reducing agent and water, stirring the reaction under ice bath conditions, washing and drying to obtain the nano-octahedral electrocatalyst (i.e., a multi-level structure Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst).
[0011] The multi-level structure means that the electrocatalyst has a core-shell structure, and the shell layer covers the nanosheet array.
[0012] In step (1), the reducing agent includes L-ascorbic acid (C6H8O6);
[0013] And / or, the soluble inorganic copper salt is selected from any one of copper nitrate, copper chloride and copper sulfate;
[0014] and / or, the surfactant comprises polyvinylpyrrolidone (PVP);
[0015] And / or, the heating reaction temperature is 80-90°C and the time is 3-6h;
[0016] and / or, the molar ratio of the soluble inorganic copper salt to the reducing agent is 1:(5-7);
[0017] And / or, the content of the surfactant in the mixed solution A is 40-60 g / L;
[0018] And / or, the drying temperature is 60-80°C and the drying time is 12-18h;
[0019] And / or, the centrifugal washing comprises centrifuging the product with water and anhydrous ethanol for at least three times each, the centrifugal speed is 6000-9500 rpm, and the time is 6-10 min.
[0020] In step (2), the vanadate is selected from sodium orthovanadate or sodium metavanadate; preferably sodium orthovanadate;
[0021] And / or, the cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride and cobalt sulfate;
[0022] and / or, the usage ratio of the Cu2O nano-octahedron, Na2S2O3, cobalt salt and vanadate is 50-100 g:1200-1300 g:0.2-0.5 mol:0.2-0.5 mol;
[0023] and / or, the concentration of the Cu2O nano-octahedron in the mixed solution is 10-20 g / L;
[0024] And / or, the stirring reaction time is 10 to 30 minutes;
[0025] And / or, the drying temperature is 60-80°C and the drying time is 12-18h;
[0026] And / or, the centrifugal washing comprises centrifuging the product with water and anhydrous ethanol for at least three times each, the centrifugal speed is 6000-9500 rpm, and the time is 6-10 min.
[0027] In step (3), the vanadate is selected from sodium orthovanadate or sodium metavanadate;
[0028] And / or, the ruthenium salt is selected from ruthenium nitrate or ruthenium trichloride;
[0029] and / or, the reducing agent comprises NaBH4;
[0030] And / or, the molar ratio of the vanadate, the ruthenium salt and the reducing agent is (5-10):(1-5):(40-50);
[0031] And / or, the temperature of the ice bath is 0-5°C;
[0032] And / or, the stirring reaction time is 10 to 30 minutes;
[0033] And / or, the drying temperature is 60-80°C and the drying time is 12-18h;
[0034] And / or, the washing comprises centrifugal washing twice with water and ethanol respectively, the centrifugal speed is 6000-9500 rpm, and the time is 6-10 min.
[0035] The second technical solution of the present invention: a nano octahedral electrocatalyst (multi-level structure Ru-(CoCu)2V2O7@Cu2O nano octahedral electrocatalyst) prepared by the above preparation method.
[0036] The multi-level structure Ru-(CoCu)2V2O7@Cu2O electrocatalyst of the present invention combines the dual characteristics of noble metals and oxygen-philic non-noble metals, can prevent over-oxidation while reducing energy consumption, and improve the selectivity of C2 products. The electrocatalyst of the present invention has a unique multi-level core-shell structure, which can enhance the structural toughness of the electrocatalyst, improve stability, and has the advantages of high efficiency, stability, low cost, good selectivity, etc. The use of the electrocatalyst can achieve the upgraded utilization of PET and energy-saving green hydrogen production.
[0037] The edge length of the multi-level structure Ru-(CoCu)2V2O7@Cu2O nano octahedron electrocatalyst is 800-1000nm.
[0038] The average particle size of the Ru-(CoCu)2V2O7 nanoparticles in the multi-level structure Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst is 50 to 80 nm; the thickness of the (CoCu)2V2O7 active layer is 60 to 100 nm;
[0039] The third technical solution of the present invention: an application of the above-mentioned nano-octahedral electrocatalyst in the preparation of hydrogen energy.
[0040] Technical solution four of the present invention: an application of the above-mentioned nano-octahedral electrocatalyst in ethylene glycol electrocatalytic oxidation (EGOR) coupled cathode hydrogen production.
[0041] The present invention discloses the following technical effects:
[0042] (1) The preparation process of the multi-level structure Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst of the present invention is simple, the conditions are mild, the time consumption is short, the cost is low, and it is suitable for large-scale production. It solves the problems of insufficient activity, poor stability, low selectivity, high energy consumption, and sluggish kinetics of existing traditional catalysts. The prepared electrocatalyst is suitable for PET plastic upgrading and coupled with efficient hydrogen production, and has the dual functions of environmental pollution control and clean energy preparation. It provides a new solution for the development of electrocatalysts in EGOR reactions, and has broad application prospects and important scientific value in the field of plastic upgrading and coupled hydrogen production.
[0043] (2) The synergistic effect of the multi-level structure and element doping endows the catalyst with remarkable electrocatalytic oxidation performance for ethylene glycol, and high value-added C2 products are selectively prepared, thus realizing the upgraded utilization of polyethylene terephthalate (PET) plastics.
[0044] (3) Compared with the traditional preparation method, the present invention realizes the multi-strategy coordinated regulation and comprehensive optimization of surface electronic properties, and has the advantages of unique morphology, adjustable composition, stable structure, etc., which can overcome the problems of high energy consumption, poor stability, low selectivity, etc. faced by EGOR catalysts under alkaline conditions. Compared with the prior art, the electrocatalyst prepared by the present invention has the following advantages:
[0045] By utilizing the synergistic effect of noble metals and oxygen-philic non-noble elements, the adsorption behavior of key intermediates (*OCCH2OH) at Ru sites is enhanced, the selectivity is improved, and high value-added C2 products can be obtained;
[0046] By element doping, the electronic structure and local coordination environment of the Co site are adjusted, the effective active sites are increased, the electron transfer is accelerated, the catalytic efficiency is improved, and the energy consumption is reduced.
[0047] The uniquely designed multi-level structure enriches the active specific surface area, shortens the mass transfer path, accelerates the diffusion rate, and at the same time enhances the structural flexibility and improves stability.
[0048] The preparation method of the present invention has universal applicability, and a series of multi-level structured nano octahedron electrocatalysts with similar morphology and structure can be obtained by simply changing the type and dosage of the soluble metal inorganic salt. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0050] Figure 1 Schematic diagram of the synthesis process of the hierarchical structure Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst;
[0051] Figure 2 XRD pattern of Cu2O nano-octahedron prepared in Example 1;
[0052] Figure 3 The SEM images of the Cu2O nano-octahedron prepared in Example 1, wherein (a) and (b) are SEM images at different magnifications;
[0053] Figure 4 XRD pattern of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1;
[0054] Figure 5This is a SEM image of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1;
[0055] Figure 6 TEM image of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1;
[0056] Figure 7 This is the EDX-Mapping diagram of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1, wherein (a) is the element Ru, (b) is the element Co, (c) is the element Cu, (d) is the element V, (e) is the element O, and (f) is all elements;
[0057] Figure 8 The SEM image and EDS linear scanning element distribution map of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1, wherein (a) is the SEM image, (b) to (f) are the distribution maps of each element, and (g) is the comprehensive distribution map of all elements;
[0058] Fig. 9 XPS graph of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1, wherein (a) is the Cu 2p spectrum, (b) is the Cu LMM Auger spectrum, (c) is the Co 2p spectrum, (d) is the Ru 3p spectrum, (e) is the V2p spectrum, and (f) is the O1s spectrum;
[0059] Fig.10 XRD pattern of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 2;
[0060] Fig.11 This is a SEM image of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 2;
[0061] Fig.12 XRD pattern of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 3;
[0062] Fig.13 This is a SEM image of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 3;
[0063] Fig.14 XRD pattern of Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Comparative Example 1;
[0064] Fig.15This is a SEM image of the Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Comparative Example 1;
[0065] Fig.16 XRD pattern of (CoCu)2V2O7@Cu2O core-shell structure nano-octahedral electrocatalyst prepared in Comparative Example 2;
[0066] Fig.17 The SEM images of the (CoCu)2V2O7@Cu2O core-shell structured nano-octahedral electrocatalyst prepared in Comparative Example 2, wherein (a) and (b) are SEM images at different magnifications;
[0067] Fig.18 LSV diagram of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 for OER and EGOR;
[0068] Fig.19 The current-potential diagram of OER and EGOR of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1;
[0069] Fig. 20 The Tafel slope diagram of OER and EGOR of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1;
[0070] Fig.21 It diagram of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 at different voltages;
[0071] Fig. 22 The Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 after EGOR test at different voltages 1 HNMR spectra;
[0072] Fig.23 LSV curves of the electrocatalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 2 in 1M KOH+1M EG electrolyte;
[0073] Fig.24 Current-potential diagrams of the electrocatalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 2 in 1M KOH+1M EG electrolyte;
[0074] Fig.25 The stability curves of the electrocatalysts prepared in Example 1 and Comparative Examples 1-2 in 1M KOH+1M EG electrolyte;
[0075] Fig.26LSV curve of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 in 1M KOH+1MEG and PET hydrolyzate;
[0076] Fig. 27 The electrooxidation products of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 in PET hydrolyzate 1 HNMR spectra;
[0077] Fig.28 The electrooxidation products of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 in PET hydrolyzate 13 C NMR spectrum. DETAILED DESCRIPTION
[0078] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0079] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0080] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0081] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0082] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0083] Unless otherwise specified, the materials in the following examples were prepared according to existing methods or directly purchased from the market.
[0084] In the following embodiments, cobalt nitrate is used as the cobalt source, but in addition, cobalt nitrate can also be replaced by cobalt sulfate or cobalt chloride, sodium vanadate can be replaced by sodium metavanadate, and ruthenium chloride can be replaced by ruthenium nitrate, thereby preparing a hierarchical structure Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst.
[0085] Example 1
[0086] A preparation method of a multi-level structure Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst:
[0087] (1) Preparation of Cu2O nano-octahedron:
[0088] 0.171 g of CuCl2·2H2O (1 mmol) solid was dissolved in 100 mL of deionized water to form a solution, and 5.556 g of PVP as a surfactant was added under uniform stirring in an oil bath at 80°C to prepare a mixed solution A;
[0089] 15 mL of a 2 mol / L NaOH solution and 10 mL of a 0.6 mol / L L-ascorbic acid solution (6 mmol) were mixed to obtain a mixed solution B.
[0090] The mixed solution A was added to the mixed solution B, and the mixture was fully stirred for 5 minutes in an oil bath at 80°C by a liquid phase diffusion method, and then the stirring was stopped. The mixture was allowed to stand for 4 hours in an oil bath at 80°C. The product was centrifugally washed 3 times with deionized water and anhydrous ethanol (the water washing was centrifuged at a centrifugal speed of 9600 rpm / min for 10 minutes; the anhydrous ethanol washing was centrifuged at a centrifugal speed of 6000 rpm / min for 6 minutes). The resulting product was then placed in a drying oven and dried at 60°C for 12 hours to obtain a Cu2O nano-octahedron (template).
[0091] (2) Preparation of (CoCu)2V2O7@Cu2O core-shell structure intermediate: 0.2mmol Co(NO3)2·6H2O, 0.2mmol Na3VO4·12H2O, and 1.24g Na2S2O3 were added into 5mL deionized water and mixed well to obtain a mixed solution;
[0092] 50 mg of Cu2O nano-octahedron powder was added to the mixed solution, stirred at room temperature for 10 min, and then centrifuged and washed three times with deionized water and anhydrous ethanol (centrifuged at 9600 rpm / min for 10 min during washing). The resulting product was then placed in a drying oven and dried at 60°C for 12 h to obtain a (CoCu)2V2O7@Cu2O core-shell structure intermediate (a (CoCu)2V2O7 active layer was generated on the surface of the Cu2O nano-octahedron through a precipitation conversion strategy, namely, the (CoCu)2V2O7@Cu2O nano-octahedron).
[0093] (3) Preparation of hierarchical Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst: 0.5 mmol Na3VO4·12H2O, 0.5 mmol RuCl3, and 4 mmol NaBH4 were added into 10 mL deionized water and mixed well to obtain a mixed solution;
[0094] The (CoCu)2V2O7@Cu2O core-shell structure intermediate prepared in step (2) is added to the mixed solution, and the reaction is stopped after stirring for 10 minutes under the reaction conditions of 0-5°C in an ice water bath. The mixture is centrifuged and washed twice with deionized water and anhydrous ethanol (the water washing is centrifuged at a centrifugal speed of 9600 rpm / min for 10 minutes; the anhydrous ethanol washing is centrifuged at a centrifugal speed of 6000 rpm / min for 6 minutes). The obtained product is then placed in a drying oven and dried at 60°C for 12 hours to obtain a multi-level structure Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst (i.e., Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst).
[0095] Schematic diagram of the synthesis process of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst Figure 1 .
[0096] The XRD pattern of the Cu2O nano-octahedron prepared in this example is shown in Figure 2 .
[0097] from Figure 2 It can be seen that all XRD diffraction peaks of the Cu2O nano-octahedron prepared in this example match the standard card of cubic phase Cu2O (JCPDS No.05-0667), indicating that the above preparation method successfully synthesized the Cu2O precursor.
[0098] The SEM image of the Cu2O nano-octahedron prepared in this example is shown in Figure 3 , Figure 3 (a) and (b) are SEM images at different magnifications.
[0099] from Figure 3It can be seen that the method of this embodiment can be used to prepare monodisperse Cu2O nano-octahedra on a large scale, with a side length of 700-900 nm, a smooth surface, a regular structure and uniform size.
[0100] The XRD pattern of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example is shown in Figure 4 .
[0101] from Figure 4 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this embodiment contains undissolved Cu2O cores, as well as Cu2V2O7 and Co2V2O7. At the same time, due to the successful doping of Ru atoms, its diffraction peak position has a slight negative shift. No other impurity phases exist, indicating that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst has been successfully synthesized.
[0102] The SEM image of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example is shown in Figure 5 .
[0103] from Figure 5 It can be seen that a Ru-doped (CoCu)2V2O7 active layer is successfully deposited on the surface of the Cu2O nano-octahedron to form a Ru-(CoCu)2V2O7@Cu2O nano-octahedron with a multi-level structure. This material inherits the nano-octahedron morphology of the Cu2O precursor, but its particle size is significantly increased, with a side length of 800 to 1000nm. The results show that the Ru-(CoCu)2V2O7@Cu2O nano-octahedron electrocatalyst synthesized by the preparation method of this embodiment has a high structural stability.
[0104] The TEM image of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example is shown in Figure 6 .
[0105] from Figure 6 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst has a multi-level core-shell structure.
[0106] Figure 7 This is the EDX-Mapping diagram of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example, where (a) is element Ru, (b) is element Co, (c) is element Cu, (d) is element V, (e) is element O, and (f) is all elements.
[0107] from Figure 7It can be seen that the catalyst contains five elements, Ru, Co, Cu, V, and O, and all elements are distributed relatively evenly without phase segregation, indicating that the precious metal Ru element is successfully doped into the (CoCu)2V2O7@Cu2O electrocatalyst.
[0108] Figure 8 SEM images and EDS linear scanning element distribution maps of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example, where (a) is the SEM image, (b) to (f) are the distribution maps of each element, and (g) is the comprehensive distribution map of all elements.
[0109] from Figure 8 As can be seen in Figure (a), the catalyst has a multi-level structure, and the measurement path of element distribution is marked in the figure.
[0110] from Figure 8 As can be seen from Figures (b) to (g), each element has a different distribution intensity on the scanning path. The results show that Ru, Co, Cu, V, and O elements are evenly distributed in the catalyst structure without obvious separation, indicating that these elements are evenly distributed in the material. Figure 7 This uniform distribution can ensure the synergistic effect of multiple active sites, thus contributing to the high activity and stability of the catalyst in electrocatalytic reactions.
[0111] Fig. 9 XPS graphs of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example, where (a) is the Cu 2p spectrum, (b) is the Cu LMM Auger spectrum, (c) is the Co 2p spectrum, (d) is the Ru 3p spectrum, (e) is the V2p spectrum, and (f) is the O1s spectrum.
[0112] from Fig. 9 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example contains Cu 2+ , Cu + 、Co 2+ 、Co 3+ 、Ru 3+ 、Ru 4+ 、V 4+ 、V 5+ .
[0113] from Fig. 9 As can be seen in Figure (b), the L shell electrons of Cu are excited and undergo Auger transition. The LMM peak helps further confirm the oxidation state of Cu, mainly Cu 2+ exist.
[0114] from Fig. 9 Figure (f) shows the 1s orbital binding energy of O, where O v , O ads and MO bonds represent oxygen vacancies, adsorbed oxygen, and metal oxygen bonds, respectively.
[0115] The above results show that the metal elements in the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst have multiple oxidation states, and the oxygen element also exists in different chemical environments. These characteristics indicate that the catalyst has a complex electronic structure and redox properties, which can enhance its activity in the electrocatalytic process.
[0116] Example 2
[0117] Same as Example 1, except that the amount of RuCl3 used in step (3) is 0.3 mmol.
[0118] The XRD pattern of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example is shown in Fig.10 .
[0119] from Fig.10 It can be seen that the characteristic diffraction peaks of Cu2V2O7, Co2V2O7 and Cu2O all exist at this ruthenium concentration, and their positions are basically consistent. This indicates that low-dose ruthenium doping has no significant change in the crystal structure of the main phase.
[0120] The SEM image of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example is shown in Fig.11 .
[0121] from Fig.11 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example has a similar structure to that of Example 1 (multi-level structure and nano-octahedral morphology).
[0122] Example 3
[0123] Same as Example 1, except that the amount of RuCl3 used in step (3) is 0.1 mmol.
[0124] The XRD pattern of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example is shown in Fig.12 .
[0125] from Fig.12 It can be seen that the characteristic diffraction peaks of Cu2V2O7, Co2V2O7 and Cu2O all exist at this ruthenium concentration, and the diffraction peak positions are basically consistent. This indicates that at this ruthenium concentration, the crystal structure of these main phases has not changed significantly.
[0126] The SEM image of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this example is shown in Fig.13 .
[0127] from Fig.13 It can be seen that compared with the RuCl3 concentration of 0.5mmol, the catalyst particles synthesized at a ruthenium concentration of 0.1mmol are significantly smaller in size, irregular in shape, and smoother in surface, lacking obvious nano-scale rough structures, indicating that the concentration of ruthenium has an influence on the growth of crystals and the formation of surface structure. A higher concentration of ruthenium makes it more conducive to the formation of a rough, nano-scale surface structure.
[0128] Comparative Example 1
[0129] Preparation method of Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst:
[0130] (1) Preparation of Cu2O nano-octahedron:
[0131] 0.171 g of CuCl2·2H2O (1 mmol) solid was dissolved in 100 mL of deionized water to form a solution, and 5.556 g of PVP as a surfactant was added under uniform stirring in an oil bath at 80°C to prepare a mixed solution A;
[0132] 15 mL of a 2 mol / L NaOH solution and 10 mL of a 0.6 mol / L L-ascorbic acid solution (6 mmol) were mixed to obtain a mixed solution B.
[0133] The mixed solution A was added to the mixed solution B, and the mixture was fully stirred for 5 minutes in an oil bath at 80°C by a liquid phase diffusion method, and then the stirring was stopped. The mixture was allowed to stand for 4 hours in an oil bath at 80°C. The product was centrifugally washed 3 times with deionized water and anhydrous ethanol (the water washing was centrifuged at a centrifugal speed of 9600 rpm / min for 10 minutes; the anhydrous ethanol washing was centrifuged at a centrifugal speed of 6000 rpm / min for 6 minutes). The resulting product was then placed in a drying oven and dried at 60°C for 12 hours to obtain a Cu2O nano-octahedron (template).
[0134] (2) Preparation of Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst: 0.5 mmol Na3VO4·12H2O, 0.5 mmol RuCl3, and 4 mmol NaBH4 were added into 10 mL deionized water and mixed well to obtain a mixed solution;
[0135] The Cu2O nano-octahedron prepared in step (2) is added to the mixed solution, and the reaction is stopped after stirring for 10 minutes in an ice water bath at 0-5°C. The mixture is centrifuged and washed twice with deionized water and anhydrous ethanol (the water washing is centrifuged at a centrifugal speed of 9600 rpm / min for 10 minutes; the anhydrous ethanol washing is centrifuged at a centrifugal speed of 6000 rpm / min for 6 minutes). The obtained product is then placed in a drying oven and dried at 60°C for 12 hours to obtain a Ru-Cu2V2O7@Cu2O nano-octahedron electrocatalyst.
[0136] The XRD pattern of the Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this comparative example is shown in Fig.14 .
[0137] from Fig.14 It can be seen that all diffraction peaks of the Ru-Cu2V2O7@Cu2O nano octahedral electrocatalyst prepared in this comparative example can identify the Cu2O and Cu2V2O7 phases, and the diffraction peak positions are slightly shifted, indicating that the Ru element is uniformly doped into the surface active phase. Therefore, the Ru-Cu2V2O7@Cu2O nano octahedral electrocatalyst is successfully synthesized.
[0138] The SEM image of the Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst prepared in this comparative example is shown in Fig.15 .
[0139] from Fig.15 It can be seen that compared with Ru-(CoCu)2V2O7@Cu2O, Ru-Cu2V2O7@Cu2O exhibits an irregular agglomerate morphology and lacks a clear geometric shape. The disordered agglomerate morphology leads to a low specific surface area and uneven distribution of active sites, which affects the activity and stability of the catalyst. This shows that the doping of Co element plays a key role in maintaining structural integrity and promoting the formation of regular morphology. The doping of Co element can make the morphology of the catalyst more uniform and stable.
[0140] Comparative Example 2
[0141] Preparation method of (CoCu)2V2O7@Cu2O core-shell structured nano-octahedral electrocatalyst:
[0142] (1) Preparation of Cu2O nano-octahedrons: 0.171 g of CuCl2·2H2O (1 mmol) solid was dissolved in 100 mL of deionized water to form a solution, and 5.556 g of PVP as a surfactant was added under uniform stirring in an oil bath at 80°C to prepare a mixed solution A;
[0143] 15 mL of a 2 mol / L NaOH solution and 10 mL of a 0.6 mol / L L-ascorbic acid solution (6 mmol) were mixed to obtain a mixed solution B.
[0144] The mixed solution A was added to the mixed solution B, and the mixture was fully stirred for 5 minutes in an oil bath at 80°C by a liquid phase diffusion method, and then the stirring was stopped. The mixture was allowed to stand for 4 hours in an oil bath at 80°C. The product was centrifugally washed 3 times with deionized water and anhydrous ethanol (the water washing was centrifuged at a centrifugal speed of 9600 rpm / min for 10 minutes; the anhydrous ethanol washing was centrifuged at a centrifugal speed of 6000 rpm / min for 6 minutes). The resulting product was then placed in a drying oven and dried at 60°C for 12 hours to obtain a Cu2O nano-octahedron (template).
[0145] (2) Preparation of (CoCu)2V2O7@Cu2O core-shell structured nano-octahedral electrocatalyst: 0.2 mmol Co(NO3)2·6H2O, 0.2 mmol Na3VO4·12H2O, and 1.24 g Na2S2O3 were added to 5 mL of deionized water to obtain a mixed solution;
[0146] 50 mg of Cu2O nano-octahedral precursor powder was added to the mixed solution, stirred at room temperature for 10 min, and then centrifuged and washed three times with deionized water (centrifuged at a centrifugal speed of 9600 rpm / min for 10 min during washing). The resulting product was then placed in a drying oven and dried at 60°C for 12 h to obtain a (CoCu)2V2O7@Cu2O core-shell structured nano-octahedral electrocatalyst.
[0147] The XRD pattern of the (CoCu)2V2O7@Cu2O core-shell structure nano-octahedral electrocatalyst prepared in this comparative example is shown in Fig.16 .
[0148] from Fig.16 It can be seen that all diffraction peaks of the (CoCu)2V2O7@Cu2O core-shell structured nano octahedral electrocatalyst prepared in this comparative example can identify Cu2O, Cu2V2O7 and Co2V2O7 phases, indicating that the (CoCu)2V2O7@Cu2O core-shell structured nano octahedral electrocatalyst was successfully synthesized.
[0149] The SEM image of the (CoCu)2V2O7@Cu2O core-shell structure nano-octahedral electrocatalyst prepared in this comparative example is shown in Fig.17 , Fig.17 (a) and (b) are SEM images at different magnifications.
[0150] from Fig.17It can be seen that the (CoCu)2V2O7@Cu2O core-shell structured nano-octahedral electrocatalyst has a regular octahedral core-shell structure, and its surface (CoCu)2V2O7 active layer forms a uniform nanosheet morphology, which is regularly loaded on the surface of the nano-octahedral shell layer.
[0151] Effect Example 1
[0152] The components of the electrocatalysts prepared in the examples and comparative examples were further analyzed by inductively coupled atomic emission spectroscopy (ICP-AES). The results are shown in Table 1.
[0153] Table 1 Inductively coupled atomic emission spectroscopy test data of the medium-power catalysts prepared in the examples and comparative examples
[0154]
[0155] Effect Example 2
[0156] (I) Preparation of working electrode:
[0157] Weigh 10 mg of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 and disperse it in 500 μL of a mixed solution containing 150 μL of 5wt.% Nafion solution and 350 μL of anhydrous ethanol, and then ultrasonicate it in an ultrasonic cell disruptor for 30 min to uniformly disperse the catalyst in the solution. The catalyst solution was then placed on an oscillator and continuously vibrated for 12 h to form a uniformly dispersed catalyst slurry. 20 μL of the above catalyst slurry was drawn with a precision pipette and dripped on a polished glassy carbon electrode sheet (GCE, 5 mm diameter) to allow it to diffuse naturally to cover the surface of the electrode sheet, and allowed to dry naturally in the air to obtain a glassy carbon electrode as a working electrode.
[0158] (II) Performance test
[0159] (1) OER and EGOR activity test of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst:
[0160] OER uses 1 mol / L potassium hydroxide solution (KOH, pH = 14.00) as the electrolyte, and EGOR uses a mixed solution of 1 mol / LKOH solution and 1 mol / LEG as the electrolyte. Hg / HgO electrode is used as the reference electrode, carbon rod electrode is used as the counter electrode, and glassy carbon electrode is used as the working electrode. The electrochemical properties of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst were tested using Shanghai Chenhua electrochemical workstation (model CHI660E or CHI760E). The OER and EGOR performances were tested using linear sweep voltammetry with a test range of 0 to 2.0 V and a scan rate of 5 mV / s. The ohmic drop caused by the solution resistance was compensated by a 95% iR correction during the test. All potentials were normalized to the potential of the reversible hydrogen electrode (RHE), and the formula was: E RHE =E Hg / HgO +0.059pH+0.098. The logarithmic values of overpotential (η) and current density (j) were processed to draw the Tafel curve, and the linear part was fitted to the Tafel equation: η=blog(j)+a, and the Tafel slope was calculated.
[0161] (2) Stability test of OER and EGOR of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst:
[0162] A test system similar to that in step (1) was used, with 1 mol / L potassium hydroxide solution (KOH, pH=14.00) as the electrolyte for OER and a mixed solution of 1 mol / L KOH solution and 1 mol / LEG as the electrolyte for EGOR. Hg / HgO electrode was used as the reference electrode, carbon rod electrode was used as the counter electrode, and glassy carbon electrode was used as the working electrode. The constant voltage stability test of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst was carried out in the potential range of 0.6 V to 1.1 V using the chronoamperometry on a Shanghai Chenhua electrochemical workstation (model CHI660E or CHI760E).
[0163] The LSV diagram of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 for OER and EGOR is shown in Fig.18 .
[0164] from Fig.18 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst EGOR prepared in Example 1 has a lower starting potential than the OER reaction, and has a higher current density response at a lower operating voltage, indicating that the catalyst has excellent EGOR catalytic activity.
[0165] The current-potential diagram of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 for OER and EGOR is shown in Fig.19 .
[0166] from Fig.19 It can be seen that at the same current density, the potential at which EGOR occurs is lower than that at which OER occurs. 2 At the current density of 2.03V, the OER reaction requires a voltage drive of 0.88V, while the EGOR reaction only requires 0.88V, and the voltage loss is reduced by 1.15V.
[0167] The Tafel slope diagram of OER and EGOR of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 is shown in Fig. 20 .
[0168] from Fig. 20 It can be seen that the Tafel slope of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 for the EGOR reaction is relatively low, only 76 mV / dec, while the Tafel slope for the OER reaction is as high as 163 mV / dec, indicating that the catalyst has a kinetic advantage in EGOR.
[0169] The it diagram of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 at different voltages is shown in Fig.21 .
[0170] from Fig.21 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 has a small current density decay when running in the potential range of 0.6V to 1.0V for 30min, and can maintain good stability.
[0171] Example 1 Preparation of Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst after EGOR test at different voltages 1 HNMR diagram Fig. 22 . Fig. 22 FA is formic acid, D2O is heavy water, GA is glycolic acid, EG is ethylene glycol, and DMSO is dimethyl sulfoxide.
[0172] from Fig. 22 It can be seen that after the EGOR process occurs at 1.1 V, the selectivity for producing C2 high value-added products (glycolic acid, GA) is the highest, indicating that this catalysis has the potential to achieve the upgrading of PET plastics.
[0173] Effect Example 3
[0174] (1) The LSV curves of the electrocatalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 2 for EGOR in 1 mol / L KOH solution and 1 mol / L EG electrolyte were measured. The measurement method was the same as that in Example 2. The results are shown in FIG. Fig.23 .
[0175] from Fig.23 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 has better EGOR activity than that of Comparative Examples 1-2, and is not much different from that of Examples 2-3. It can still have a higher current response even at a lower operating voltage, indicating that the synergistic effect of the noble metal Ru and the oxygen-philic non-noble element Co plays an important role in improving the EGOR activity of the catalyst.
[0176] The Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Comparative Example 1 has better EGOR activity than that of Comparative Example 2, but is much lower than that of Examples 1 to 3, indicating that the cobalt element also plays an important role in improving the EGOR activity of the catalyst.
[0177] The EGOR activity of the (CoCu)2V2O7@Cu2O core-shell structured nano-octahedral electrocatalyst prepared in Comparative Example 2 is the lowest, much lower than that of Examples 1 to 3, and slightly lower than that of Comparative Example 1, indicating that ruthenium plays an important role in improving the EGOR activity of the catalyst.
[0178] (2) The current-potential of the electrocatalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was measured in 1 mol / L KOH solution and 1 mol / L EG electrolyte. The measurement method was the same as that in Example 2. The results are shown in Fig.24 .
[0179] from Fig.24 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 has better electrochemical performance than the electrocatalysts prepared in Examples 2-3 and Comparative Examples 1-2, and can produce a larger current density at the same voltage. When the anode decomposition voltage is 1.0V, the current density of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 for EGOR is as high as 429mA / cm 2 , much higher than that of comparative example 1 (142 mA / cm 2 ) and Comparative Example 2 (43 mA / cm 2 ).
[0180] from Fig.24It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 2 has higher EGOR catalytic performance than the electrocatalysts prepared in Comparative Examples 1-2. When the voltage is 1.0 V, its current density is 380 mA / cm 2 , that is, it can produce a larger current density under the same voltage.
[0181] from Fig.24 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 3 has better electrochemical performance than the electrocatalysts prepared in Comparative Examples 1 to 2, and can produce a larger current density at the same voltage.
[0182] from Fig.24 It can be seen that the Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Comparative Example 1 has better electrochemical performance than the electrocatalyst prepared in Comparative Example 2, and can produce a larger current density at the same voltage, but is much lower than Examples 1 to 3.
[0183] from Fig.24 It can be seen that the (CoCu)2V2O7@Cu2O core-shell structured nano-octahedral electrocatalyst prepared in Comparative Example 2 has the lowest EGOR catalytic activity and can only produce the minimum current density at the same voltage, which is much lower than Examples 1 to 3 and slightly lower than Comparative Example 1.
[0184] (3) The stability curves (1.0 V (vs. RHE)) of the electrocatalysts prepared in Example 1 and Comparative Examples 1-2 were measured in 1 mol / L KOH solution and 1 mol / L EG electrolyte. The measurement method was the same as that in Effect Example 2. The results are shown in Fig.25 .
[0185] from Fig.25 It can be seen that the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 has better stability than that of Comparative Examples 1 to 2, and the current density does not show obvious attenuation even after 40 hours of continuous operation.
[0186] from Fig.25 It can be seen that the current density of the Ru-Cu2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Comparative Example 1 is relatively low and decays rapidly, indicating that its stability and activity are not as good as those in Example 1, but slightly higher than those in Comparative Example 2, indicating that the cobalt element plays an important role in improving the stability and activity of the catalyst.
[0187] from Fig.25It can be seen that the current density of the (CoCu)2V2O7@Cu2O core-shell structure nano octahedron electrocatalyst prepared in Comparative Example 2 is the lowest and the attenuation is the most obvious, indicating that its stability and activity are far inferior to those in Example 1 and Comparative Example 1, indicating that ruthenium plays the most important role in improving the stability and activity of the catalyst.
[0188] Effect Example 4
[0189] (1) The LSV curve of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 in 1M KOH+1MEG or PET hydrolyzate (PET hydrolyzate is a hydrolyzate prepared by dissolving PET in 1 mol / L KOH) is measured. The results are shown in Fig.26 .
[0190] from Fig.26 It can be seen that the LSV curves of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 in 1M KOH+1M EG and PET hydrolyzate almost overlap, proving that the catalyst has significant EGOR electrocatalytic performance for PET hydrolyzate, showing the application potential for upgrading and utilizing PET plastics.
[0191] (2) Determination of the electrooxidation product of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 in PET hydrolyzate 1 H NMR spectrum, see Fig. 27 . Fig. 27 FA is formic acid, TPA is terephthalic acid, D2O is heavy water, GA is glycolic acid, EG is ethylene glycol, and DMSO is dimethyl sulfoxide.
[0192] from Fig. 27 It can be seen that the main product of PET hydrolysate after electro-oxidation is the high value-added C2 product glycolic acid (GA), and only a very small amount of EG is peroxidized to low value-added chemical formic acid (FA), which has excellent selectivity. At the same time, the presence of TPA in PET hydrolysate has almost no effect on the EGOR process, further proving that the catalyst has great application potential in the direction of electrocatalytic upgrading of PET plastics to high value-added GA products.
[0193] (3) Determination of the electro-oxidation product of the Ru-(CoCu)2V2O7@Cu2O nano-octahedral electrocatalyst prepared in Example 1 in PET hydrolyzate 13 C NMR spectrum, see Fig.28 .
[0194] from Fig.28 It can be seen that the main product of PET hydrolysate after electro-oxidation is GA, and the by-product is FA. Fig. 27 The conclusions are consistent, proving that the catalyst has great application potential in the electrocatalytic upgrading of PET plastics to high-value-added GA products.
[0195] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a nano-octahedral electrocatalyst, characterized in that: The following steps are involved: The Cu2O nano-octahedron is used as a template, a (CoCu)2V2O7 active layer is deposited on its surface through a precipitation conversion strategy, and then Ru is doped to obtain the nano-octahedron electrocatalyst.
2. The preparation method according to claim 1, characterized in that: The method for preparing the Cu2O nano-octahedron comprises the following steps: A mixed solution B of an alkali and a reducing agent is added to a mixed solution A of a soluble inorganic copper salt and a surfactant, and the mixture is heated for reaction to obtain the Cu2O nano-octahedron.
3. The preparation method according to claim 2, characterized in that: The reducing agent includes L-ascorbic acid; and / or, the surfactant comprises polyvinyl pyrrolidone; And / or, the heating reaction temperature is 80-90°C and the time is 3-6h; and / or, the molar ratio of the soluble inorganic copper salt to the reducing agent is 1:(5-7); And / or, the content of surfactant in the mixed solution A is 40-60 g / L.
4. The preparation method according to claim 1, characterized in that: The method of depositing a (CoCu)2V2O7 active layer on the surface of the substrate by a precipitation conversion strategy comprises: The Cu2O nano-octahedrons are dispersed in a mixed solution of Na2S2O3, vanadate and cobalt salt, and stirred to react to obtain a (CoCu)2V2O7@Cu2O core-shell structure intermediate.
5. The preparation method according to claim 4, characterized in that: The vanadate is selected from sodium orthovanadate or sodium metavanadate; And / or, the cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride and cobalt sulfate; and / or, the usage ratio of the Cu2O nano-octahedron, Na2S2O3, cobalt salt and vanadate is 50-100 g:1200-1300 g:0.2-0.5 mol:0.2-0.5 mol; And / or, the stirring reaction time is 10 to 30 minutes.
6. The preparation method according to claim 5, characterized in that: The doping Ru comprises: The (CoCu)2V2O7@Cu2O core-shell structure intermediate is dispersed in a mixed solution of vanadate, ruthenium salt, reducing agent and water, and stirred for reaction under ice bath conditions to obtain the nano octahedral electrocatalyst.
7. The preparation method according to claim 6, characterized in that: The vanadate is selected from sodium orthovanadate or sodium metavanadate; And / or, the ruthenium salt is selected from ruthenium nitrate or ruthenium trichloride; and / or, the reducing agent comprises NaBH4; And / or, the molar ratio of the vanadate, the ruthenium salt and the reducing agent is (5-10):(1-5):(40-50); And / or, the stirring reaction time is 10 to 30 minutes.
8. A nano-octahedral electrocatalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the nano-octahedral electrocatalyst according to claim 8 in hydrogen energy production.
10. Use of the nano-octahedral electrocatalyst according to claim 8 in electrocatalytic oxidation coupled cathode hydrogen production.
Citation Information
Patent Citations
Core-shell structure Cu2O (Co, Cu) (OH) 2 nanocube electrocatalyst and preparation and application thereof
CN115637456A
Synthesis and application of hollow nanocube C-coated (CoZn) 3V2O8 electrocatalyst
CN117626326A